Acúmulo e carreamento de metais pesados e sólidos em superfícies asfálticas - Silva, Emanoelle Pereira da (2014)
This work aimed to quantify the build-up and wash-off pollutants in urban asphalt surfaces, mainly metals and solids, correlating the pollutant load with dry days, traffic load and rainfall intensity. The relationship between metals and particle size has been also evaluated. To do this, three streets with different traffic load as study area in Goiânia City were selected. The sediments samples were collected in six plots of 0,5 m² located in the central track of the streets during 14 days, collecting samples on 1°, 2°, 3°, 5°, 7° e 14° dry days by the vacuuming and sweeping method. For water sampling two rainfall intensities were selected to be simulated, through a simulated rainfall over an area of 3m², being on low and other high intensity, respectively 25 mm/h and 115 mm/h both with 15 minutes duration. Were simulated three events on the same experimental plot in witch study area and collected 5 water samples during witch rainfall event, which were analyzed by concentration of suspend and dissolved solids, DQO, conductivity and the metals copper, chromium, lead, cadmium, zinc, iron and manganese, determined by Atomic Absorption Spectroscopy. The results showed that build-up has a strong direct relationship with dray days and an inverse relationship with traffic load. For metals in sediments was verified that the higher concentrations are on particles < 63μm, and follow in general the concentration order Fe > Mn > Cu > Pb > Zn > Cd > Cr. The runoff water quality was observed that all the parameters analyzed, except chromium, were detected on selected study areas. The influence of rainfall intensity on wash-off pollutants was observed that this has fundamental importance, so that higher intensity wash-off a higher mass of solids and metals.